MEKANISME REKRUTMEN CALON LEGISLATIF PEREMPUAN DI PARTAI DEMOKRAT PADA PEMILU DPR RI 2024 - Putri, Anantasya -; -, Fitriyah -; Astuti, puji - (Journal of Politic and Government Studies, 2024)
Political recruitment is the function of political parties to select and select potential leaders, both at the national leadership level and within the party. Equal opportunities to participate in the world of politics and play an important role in building democracy are important things to do, therefore political parties are obliged to provide space and certainty for women to enter the world of politics. The Democratic Party was chosen as the research location because the Democratic Party has succeeded in meeting the threshold for women's representation of 30% over the last 10 years and ensuring women's representation in its leadership structure. The aim of this research is to analyze the recruitment mechanism for female legislative candidates. The theories used in this research are political party recruitment theory, women's representation and gender equality theory. The results of this research found that in the mechanism for recruiting legislative candidates, the Democratic Party pays attention to equality and justice, the Democratic Party provides equal opportunities for men and women to be involved in filling positions in politics, especially in the legislative candidacy for the DPR RI in the 2024 election without implementing treatment different for male and female legislative candidates. It is hoped that this research can provide a better understanding of the recruitment mechanisms for female legislative candidates in the Democratic Party. Furthermore, this research can serve as a guide for improving political education for women and providing more specific support for female legislative candidates